2022
DOI: 10.1007/s00277-022-04831-w
|View full text |Cite
|
Sign up to set email alerts
|

Immune reconstitution and survival of patients with parvovirus B19 related pure red cell aplasia after haplo-PBSCT

Abstract: Parvovirus B19 (PvB19) infection and PvB19 related pure red cell aplasia (PRCA) in recipients with allogeneic hematopoietic stem cell transplantation have been reported sporadically. However, clinical studies with large sample sizes are lacking, especially in patients undergoing HLA-haploidentical peripheral blood stem cell transplantation (haplo-PBSCT). In addition, clinical features, immune reconstitution, and outcomes of these patients are not clear. We conducted a retrospective analysis of 164 patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Notably, a study has suggested that patients with PvB19‐related PRCA have slower immune reconstitution after human leukocyte antigen‐haploidentical peripheral blood stem cell transplantation. 13 Another case described immune reconstitution syndrome associated with B19‐induced PRCA during highly active antiretroviral therapy. 14 Furthermore, Ye Rebecca's retrospective analysis of 177 patients with MM who underwent ASCT revealed that clonal isotype switch (CIS) was found in 39 (22%) of the cases.…”
Section: Figurementioning
confidence: 99%
“…Notably, a study has suggested that patients with PvB19‐related PRCA have slower immune reconstitution after human leukocyte antigen‐haploidentical peripheral blood stem cell transplantation. 13 Another case described immune reconstitution syndrome associated with B19‐induced PRCA during highly active antiretroviral therapy. 14 Furthermore, Ye Rebecca's retrospective analysis of 177 patients with MM who underwent ASCT revealed that clonal isotype switch (CIS) was found in 39 (22%) of the cases.…”
Section: Figurementioning
confidence: 99%